REAKTUALISASI EPISTEMOLOGI FIKIH PEREMPUAN: KAJIAN PEMIKIRAN MUTAWALLI AL-SYA’RAWI DALAM KONTEKS INDONESIA - Nurravi Alamsyah, Muhammad; Alamsyah, Muhammad Nurravi Alamsyah (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
Not a few religious texts are ad hoc. This is because revelation was revealed in order to respond to certain social symptoms at that time. Religious epistemology that talks about womanhood may be less relevant to be actualized in the modern context, because there has been a shift in various aspects. Thus, Islamic law needs to be actualized by dialoguing the text with the context. This research identifies al-Sha'rawi's istinbat paradigm in the reactualization of women's fiqh epistemology. There are four topics in this study: intellectual and religious traditions of women; verses about beating; verses about polygamy; verses about testimony. The research approach used is a doctrinal approach. Methodical steps used through qualitative methods with data collection fromlibrary research. The conclusions of the four epistemologies of women's fiqh that have been described are: First: the mind and religion of women in al-Sha'rawi's thinking are in line with Indonesian regulations, which both provide broad access to women in spiritual and intellectual matters. Second, polygamy. Al-Sha'rawi's thinking is in line with Indonesian regulations, which are legal with strict conditions. Third, beatings. Al-Sha'rawi's thinking is less relevant to the Indonesian context and regulations, because Indonesia has regulated sexual violence, both physically and psychologically. Fourth, women's testimony. Al-Sha'rawi's thinking is less relevant to the Indonesian context, where al-Sha'rawi still affirms the conventional concept of female witnesses, namely half of men. Keywords: Reactualization, Epistemology Of Women's Jurisprudence, Mutawalli Al-Sha’rawi